In silico analysis, molecular modeling and docking of pseudomonas aeruginosa putative choline kinase - Almakfoukh, Abdonasr Mohamed Ali (2021)
Pseudomonas aeruginosa is a major player in the bacterial invasion. Treating P. aeruginosa infections has become a serious challenge due to the bacterium's ability to survive several of the currently available medicines. To put an end to the antimicrobial resistance (AMR) issue, the quest for novel antimicrobics has been a key focus in the relevant research community. The AMR phenomenon has been evolving at a breakneck pace that has not been matched by the development of new drugs. As a result, innovative antimicrobials are urgently needed. Repurposing current medications allows for the development of novel antimicrobials. Choline kinase inhibitors (ChoKIs) could be one of these cutting-edge antimicrobials that puts an end to AMR once and for all. ChoKIs, which are used as anticancer drugs in human, have the potential to inhibit P. aeruginosa choline kinase (PaChoK). Inhibition of choline kinase would disrupt the synthesis of lipopolysaccharide/lipoteichoic acid molecules that are required for the bacterial cell membrane integrity. This study aims to characterize the basic properties of PaChoK by in silico approaches and generate the model structure of this enzyme for further molecular docking with ChoKI to assess the potential of utilizing ChoKIs as antimicrobial agent against P. aeruginosa. Basic bioinformatic analysis shows that PaChoK is abundant with alanine amino acids, has copious negatively charged residues and low solubility if expressed in Escherichia coli. Multiple amino acid sequence alignment and protein structure superimposition revealed homology between human and P. aeruginosa choline kinases, indicating the ChoKIs previously used to inhibit human choline kinase as potential anti-PaChoK. The model structure of PaChoK was generated and used for docking with hemicholinium- 3 (HC-3), a well known human ChoK inhibitor. The docking results showed feasible HC-3 interaction inside the choline-binding pocket of PaChoK, which interacts with seven pocket residues. The evidence clearly supports the ChoKIs such as Hemicholinium-3 appropriateness as anti-PaChoK that can be further develop into antimicrobials. Yet, experimental validation of ChoKIs interaction with and inhibition of PaChoK is still required to search for the most potent ChoKIs that can end AMR of P. aeruginosa.